Functional Characterization of Olfactory Receptors in the Thyroid Gland - Weidinger, Daniel; Jovancevic, Nikolina; Zwanziger, Denise; Theurer, Sarah; Hönes, Judith; Führer, Dagmar; Hatt, Hanns (Frontiers in Physiology, 2021)
Olfactory receptors (ORs) are almost ubiquitously expressed in the human body. However, information about their functions in these tissues is lacking. To date, no functional characterization of expressed olfactory receptors in the human thyroid has been performed. In this study, we detected and compared the expression of OR2H2 and OR2W3 in healthy and malignant cell lines and their corresponding tissues, respectively. We demonstrated that stimulation of ORs by their specific ligand resulted in a transient increase in intracellular calcium and cAMP concentrations. In the case of OR2H2, the downstream signaling cascade analysis revealed that adenylate cyclase and phosphoinositide phospholipase C were involved. Furthermore, OR2H2 and OR2W3 activation affected migration, proliferation, and invasion. These are the first insights that ORs influence physiology-relevant processes in the healthy and malignant thyroid.